LAB WORK TEXTBOOK OF FERMENTATION ENGINEERING TECHNOLOGY - Elizah Mohamed; Noor Akhmazillah Mohd Fauzi; Masayu Maslan (2023)
This textbook (Lab Work of Fermentation Engineering Technology in Chemical Engineering Technology) presents the hands-on activities that can be performed by students from Bachelor of Chemical Engineering Technology, UTHM, which relates to fundamental of bioreactor. This module is a student’s guideline for performing experimental works for biomass production of baker’s yeast (S. cerevisiae) by bioreactor and shake flask fermentation. In Chapter 1 (inoculum preparation and sterilisation technique), students are exposed to sterile technique in preparing yeast colonies and that exponential phase is determined through generated growth profile. Next in Chapter 2 (bioreactor configuration), the setting up of bioreactor and its important components are highlighted. As for Chapter 3, media that have specific formulation for the growth of yeast are prepared and autoclaved. In Chapter 4 (shake flask fermentation), the efficiency of shake flask fermentation is assessed in terms of cell concentration, substrate utilisation, growth kinetics as well as yield of S. cerevisiae. Meanwhile, Chapter 5 (production of biomass using a batch bioreactor) investigates the performance of batch bioreactor in producing biomass based on the same parameters in Chapter 4. For Chapter 6 (analytical method), detailed procedures to carry out and calculate cell concentration, glucose consumption and yield of biomass are outlined. Finally in Chapter 7 (KLa measurement), the effects of air flowrate, agitation speed and salt on oxygen transfer rate (OTR) are investigated.